2020
DOI: 10.1021/acsami.9b20568
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Axially Chiral Platinabinaphthalenes with Aggregation-Induced Emission for Red Circularly Polarized Phosphorescent Organic Light-Emitting Diodes

Abstract: Circularly polarized luminescent (CPL) materials have received a lot of interest due to their potential applications in next-generation displays. However, the development of easily accessible red circularly polarized phosphorescent emitters for practical organic light-emitting diodes fabrication remains a grand challenge. In this paper, we report a new family of CPL-active platinum complexes based on the binaphthalene chiral platform. These axially chiral platinabinaphthalenes were facile synthesized by direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 55 publications
1
42
1
1
Order By: Relevance
“…Recently, Matthew J. Fuchter’s group reported a CP-LED with a high dissymmetry factor ( g lum = 0.2) based on a platinahelicene . Zhipeng Liu’s group reported that a axially chiral platinabinaphthalene displays aggregation-induced circularly polarized phosphorescence with a high Φ PL and lower g lum of about 2.6 × 10 –3 . Youngmin You’s group adopted a binary coassembly strategy in solution deposition to realize a higher photoluminescence g lum value of 6.2 × 10 –2 ; unfortunately, the photoluminescence quantum yield is very low (Φ PL = 0.01) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Matthew J. Fuchter’s group reported a CP-LED with a high dissymmetry factor ( g lum = 0.2) based on a platinahelicene . Zhipeng Liu’s group reported that a axially chiral platinabinaphthalene displays aggregation-induced circularly polarized phosphorescence with a high Φ PL and lower g lum of about 2.6 × 10 –3 . Youngmin You’s group adopted a binary coassembly strategy in solution deposition to realize a higher photoluminescence g lum value of 6.2 × 10 –2 ; unfortunately, the photoluminescence quantum yield is very low (Φ PL = 0.01) .…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the excellent circularly polarized luminescence (CPL) emission materials need to meet the basic requirements on both the high luminescence dissymmetry factor ( g lum ) and fluorescent quantum yield (QY). Although there are more and more reports on CPL-active emission materials in the past decade, among them, most of these CPL emissive materials could not satisfy the real application necessity due to the low dissymmetry factor ( g lum ) values in the range of 10 –5 to 10 –2 . To date, many works have been payed close attention to chiral emissive nematic liquid crystals (N*-LCs) as CPL-active materials because the highly regular arrangement of N*-LCs has been proved to successfully regulate the increase of the CPL g lum value. Moreover, aggregate-induced emission (AIE) active chiral dyes as CPL emitters in LCs have been regarded as one of the most promising CPL materials since these chiral AIE-active chromophores in the aggregated state could greatly promote high QY and g lum of CPL. …”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28] Nevertheless, designs trategies that employa mino acids and sugars lead to AIEgens with poor thermal stability that lacks cope forw avelengthtunability.B INOL, vastly explored in asymmetric catalysis [29][30][31][32][33] and bearing at remendous resemblance to the rotorlike structures of typical AIEgens such as tetraphenylethene (TPE) or tetraphenylsiloles, has been used to design chiralluminogens through the appendage of well-known AIEgensa ta ppropriate positions of BINOL ( Figure 1). [34][35][36] However, these existing design strategies are mostly limited to scaffolds such as TPE or tetraphenylsiloles. The dearth of protocols to generate chiral AIEgens withouta ny AIEgens (e.g.,T PE or tetraphenylsilole) externally tagged to the chiral scaffold remains al ongstanding challenge.…”
Section: Introductionmentioning
confidence: 99%